Uji Coba Subtitusi Rumput Laut Merah (Porphyra) Dengan Daun Cincau Hijau (Cyclea Barbata Miers) Dalam Pembuatan Nori - Abduh, Mohammad Syaltut; Maulana, Alifatqul (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2018)
This study aims to utilize seaweed as a substitute on Japanese Nori foodstuffs and can be consumed by the community. Seaweed is a raw material that is widely used for various purposes such as additional ingredients on cosmetics or or just made in addition to the drink on ice mix. With this research is expected to seaweed in the making of Nori can be replaced with green grass jelly. Because Japanese food such as Nori is now commonly found in almost all major cities in Indonesia. The method used is an experimental method which will be making products with the trial of the treatment of the control over the products studied were Nori. After conducting experiments then performed using the Sensory Testing instrument in the form of a questionnaire about Organoleptik Test and Test hedonic committed to the panelists, to find out the differences as well as the level of preference on taste, texture and aroma. Descriptive test was then performed to give a snapshot of data from Appearance and hedonic test has been done. Then do the data analysis using the Test Independent T-test to determine significant differences between the arithmetic mean of the control and treatment products.